2020
DOI: 10.3389/fvets.2020.591556
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Heinz Body Anemia in a Cat After Repeat Propofol Administration Case Report

Abstract: Heinz body formation has been reported in cats repeatedly administered propofol for anesthesia induction, although the resultant changes were deemed of little clinical significance (1, 2). This report suggests repeated propofol administration to some individual cats might induce anemia with clinical signs and cessation of propofol administration may result in rapid resolution. A 9-years-old American Domestic Shorthair cat receiving a 20-fraction radiation protocol for lateral thoracic fibrosarcoma showed letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Heinz body formation occurs as a result of oxidative damage to hemoglobin and can result in hemolysis [74]. In cats, increased Heinz body formation has previously been shown to be associated with the administration of certain drugs and components, such as propofol [75], acetaminophen [76], or propylene glycol [77]. Therefore, it seems possible that there is an association between the repeated administration of Xraphconn ® and Heinz body formation in this cat.…”
Section: Discussionmentioning
confidence: 84%
“…Heinz body formation occurs as a result of oxidative damage to hemoglobin and can result in hemolysis [74]. In cats, increased Heinz body formation has previously been shown to be associated with the administration of certain drugs and components, such as propofol [75], acetaminophen [76], or propylene glycol [77]. Therefore, it seems possible that there is an association between the repeated administration of Xraphconn ® and Heinz body formation in this cat.…”
Section: Discussionmentioning
confidence: 84%
“…Most of these studies have reported that the anemia is not clinically relevant. However, in 2 studies, signs were clinically relevant 159,160 . In 1 study, malaise, anorexia, diarrhea, facial edema, and increased recovery time also were reported 159 .…”
Section: Third‐line Treatmentmentioning
confidence: 97%
“…However, in 2 studies, signs were clinically relevant. 159,160 In 1 study, malaise, anorexia, diarrhea, facial edema, and increased recovery time also were reported. 159 Based on these studies in cats, the total accumulated dose as well as the duration of propofol administration may be important factors for propofol-related adverse effects.…”
Section: Rationalementioning
confidence: 98%
See 1 more Smart Citation
“…Lower doses may be sufficient given the severity of paralysis experienced by patients with elapid envenomation ( 5 , 75 ). Recognized adverse effects include hypotension and Heinz body anemia in cats receiving multi-dosing or CRIs ( 76 , 77 ).…”
Section: Anesthetic Considerationsmentioning
confidence: 99%